Disparities in influenza vaccination across the United States: Variability by minority group, Asian sub-populations, socio-economic status, and health insurance coverage. (September 2016) - Budhwani, H.; De, P.
Abstract: Objective: The aim of this study is to examine the effects of ethnicity, disaggregating Asian Indian from other Asians, health insurance coverage, and nativity on influenza vaccination rates in the United States. Study design: National Health Interview Survey data (2013), collected by the National Center for Health Statistics, were analysed. Methods: Multivariable regression models were used to compute estimates and 95% confidence intervals. Results: Asian Indians had higher proportions of college graduate rates (mean = 0.85; CI = [0.80, 0.90]) and above-average income (mean = 0.56, CI = [0.48, 0.64]) than both Whites (mean = 0.406; CI = [0.39, 0.42]) and other Asian sub-groups, such as Chinese (mean = 0.544; CI = [0.47, 0.62]) and Filipino Americans (mean = 0.419; CI = [0.35, 0.48]). However, this higher socio-economic status did not uniformly translated into higher vaccine uptake rates. Asian Indian influenza vaccine uptake rate (mean = 0.403; CI = [0.33, 0.47]), while higher than Whites (mean = 0.366; CI = [0.36, 0.38]), were lower than Chinese (mean = 0.435; CI = [0.35, 0.52]) and Filipino Americans (mean = 0.431; CI = [0.37. 0.49]). In regression models, although Asian Indians were significantly more likely to receive the influenza vaccine than White Americans before controlling for health insurance status (OR = 1.38; CI = [1.004, 1.899]), when coverage was included, effects of race and ethnicity were eliminated (OR = 1.24; CI = [0.897, 1.705]). Conclusion: Health disparities research often analyses Asians as a homogenous mass; however, the availability of disaggregated data allows researchers to parse effects leading to nuanced findings which highlight behavioural diversity within groups. Findings may inform the development of targeted interventions by public health practitioners and adjustments to polices designed to improve health insurance coverage in racial and ethnic minorities, regardless of citizenship status, leading to enhanced population health. Highlights: Addresses race, ethnicity, and insurance coverage as associates of vaccination. Focusses on a growing yet under-researched group, Asian Indians, in the US. Asian Indians had higher influenza vaccination coverage than Whites. Income and health insurance status were better predictors of vaccination than race. Improving insurance coverage may positively influence influenza vaccination rates.